Association of cyclin‐dependent kinase inhibitor 2A/B with increased risk of developing breast cancer. Issue 6 (12th November 2019) - Seifi, Sima; Pouya, Farzaneh; Rahmani, Mahsa; Mehramiz, Mehrane; Rastgar‐Moghadam, Azam; Gharib, Masoumeh; Rahmani, Farzad; Shahidsales, Soodabeh; Hassanian, Seyed Mahdi; Khazaei, Majid; Dadjoo, Parisa; Parvin, Seyede Sara; et al.
Abstract: There is a growing body of data reporting the association of genetic alterations in chromosome 9P21 with the risk of developing cancer. In the current study, we studied the association of a genetic variant in CDKN2A/B, rs1333049, with the risk of developing breast cancer. A total of 339 participants with and without breast cancer entered to the study. Genotyping was done by the TaqMan real‐time polymerase chain reaction (RT‐PCR) method and gene expression analysis was ran by RT‐PCR. Our data showed that the minor allele homozygote in the total population was 10%, whereas for heterozygote was 38%. The dominant genetic model demonstrated that individuals with breast cancer had advanced TNM classification. Moreover, the logistic regression revealed that individuals who had CC/CG genotypes might have an enhanced risk of developing breast cancer when compared to the holders of GG genotype (e.g., OR = 2.8; 95% CI, 1.4–5.4; p =  .001), after regulated for confounders; age and body mass index. Furthermore, our analysis showed that the CDKN2A/B gene was downregulated in patients ( p  < .001). We showed a meaningful relationship of CDKN2A/B with the risk of breast cancer, cancer, showing the importance of studies in great sample size and several centers for studying the value of the marker as a risk classification in the management of patients with breast cancer.